SOMANZ guidelines for the investigation and management sepsis in pregnancy. (3rd July 2017) - Bowyer, Lucy; Robinson, Helen L.; Barrett, Helen; Crozier, Timothy M.; Giles, Michelle; Idel, Irena; Lowe, Sandra; Lust, Karin; Marnoch, Catherine A.; Morton, Mark R.; Said, Joanne; Wong, Maggie; et al.
Abstract : SOMANZ (Society of Obstetric Medicine Australia and New Zealand) has written a guideline to provide evidence‐based guidance for the investigation and care of women with sepsis in pregnancy or the postpartum period. The guideline is evidence‐based and incorporates recent changes in the definition of sepsis. The etiology, investigation and treatment of bacterial, viral and non‐infective causes of sepsis are discussed. Obstetric considerations relevant to anaesthetic and intensive care treatment in sepsis are also addressed. A multi‐disciplinary group of clinicians with experience in all aspects of the care of pregnant women have contributed to the development of the guidelines. This is an executive summary of the guidelines.